2018
DOI: 10.1038/s41467-018-04291-9
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafast probes of electron–hole transitions between two atomic layers

Abstract: Phase transitions of electron–hole pairs on semiconductor/conductor interfaces determine fundamental properties of optoelectronics. To investigate interfacial dynamical transitions of charged quasiparticles, however, remains a grand challenge. By employing ultrafast mid-infrared microspectroscopic probes to detect excitonic internal quantum transitions and two-dimensional atomic device fabrications, we are able to directly monitor the interplay between free carriers and insulating interlayer excitons between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Regarding the origin of this robust slow feature, the above ultrafast electronic excitation can be safely ruled out due to the distinct timescale. We note that the formation of the interlayer exciton also induces a bleaching signal in the TA response 47 . This process is also very fast, with the induced carrier density peaking at~1 ps and completely decaying at~20 ps, completely different from the slow peaking time of 150 ps in our measurement.…”
Section: Resultsmentioning
confidence: 76%
“…Regarding the origin of this robust slow feature, the above ultrafast electronic excitation can be safely ruled out due to the distinct timescale. We note that the formation of the interlayer exciton also induces a bleaching signal in the TA response 47 . This process is also very fast, with the induced carrier density peaking at~1 ps and completely decaying at~20 ps, completely different from the slow peaking time of 150 ps in our measurement.…”
Section: Resultsmentioning
confidence: 76%
“…3D, we show calculated QY versus ℏν with φ B of 0.6 to 0.8 eV and experimental QY values mostly fall into the calculated range. The φ B 0.2 to 0.3 eV smaller than values from quasi-particle band alignment can be attributed to interlayer exciton binding energy, which is 0.2 to 0.3 eV in two-dimensional layered heterostructures ( 36 , 37 , 43 ). Considering no free parameters, this simple 2μPTE model reproduced the experimental results reasonably well and captured the key essence: the highly efficient harnessing of energetic electron from intraband scattering, prevailing over energy and carrier loss due to interband scattering and phonon emission.…”
Section: Resultsmentioning
confidence: 85%
“…Fitting the kinetics yields a rising time of 27 ± 4 fs and a biexponential decay with a half-life time of ~1.2 ps, which corresponds to hot electron transfer from graphene to WS 2 and subsequent back electron transfer to graphene, respectively. Previous studies on graphene-TMD van der Waals heterostructures also reported an ultrafast interfacial process, mostly limited by experimental time resolution ( 27 , 36 , 40 ). This interfacial electron transfer time is orders of magnitude faster than the value (~40 ps) inferred from photocurrent measurement ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the type II band alignment, the CBM and VBM are in different layers that lead to the spatial separation of electrons and holes. The ultrafast separation of electron–hole pairs could be detected by the pump–probe technique [ 48 , 62 , 63 ]. In the WS 2 /MoS 2 heterostructure, after the MoS 2 monolayer is directly pumped the photo-induced signal will appear instantaneously.…”
Section: Propertiesmentioning
confidence: 99%